Expanding horizons and navigating challenges for enhanced clinical workflows: ChatGPT in urology - Talyshinskii, Ali; Naik, Nithesh; Hameed, B. M Zeeshan; Zhanbyrbekuly, Ulanbek; Khairli, Gafur; Guliev, Bakhman; Juilebø-Jones, Patrick; Tzelves, Lazaros; Somani, Bhaskar Kumar (Frontiers in Surgery, 2023)
Purpose of review: ChatGPT has emerged as a potential tool for facilitating doctors' workflows. However, when it comes to applying these findings within a urological context, there have not been many studies. Thus, our objective was rooted in analyzing the pros and cons of ChatGPT use and how it can be exploited and used by urologists.Recent findings: ChatGPT can facilitate clinical documentation and note-taking, patient communication and support, medical education, and research. In urology, it was proven that ChatGPT has the potential as a virtual healthcare aide for benign prostatic hyperplasia, an educational and prevention tool on prostate cancer, educational support for urological residents, and as an assistant in writing urological papers and academic work. However, several concerns about its exploitation are presented, such as lack of web crawling, risk of accidental plagiarism, and concerns about patients-data privacy.Summary: The existing limitations mediate the need for further improvement of ChatGPT, such as ensuring the privacy of patient data and expanding the learning dataset to include medical databases, and developing guidance on its appropriate use. Urologists can also help by conducting studies to determine the effectiveness of ChatGPT in urology in clinical scenarios and nosologies other than those previously listed.